Merajut Spiritualitas Dan Lingkungan: Tinjauan Teologis Terhadap Keselamatan Alam - Maria Ayu Andira; Despy Pallu; Indah Sari; Heni Maria (LPPM - STT Kadesi Bogor, 2024)
Although religious teachings emphasize the importance of respecting nature, there is a gap in integrating these values ​​into concrete actions to save the environment. This research explores strategies for building dialogue and collaboration between theological thought, science, and other stakeholders. The methods used include analysis of literature related to spiritual values ​​and environmental ethics in various religious traditions, as well as case studies of good practices in integrating spirituality into environmental efforts. The results reveal several strategies such as environmental literacy education in religious communities, involving religious leaders in advocacy, building interfaith and multisectoral partnerships, and developing environmentally friendly spiritual practices. This research emphasizes the great opportunity of religion as a catalyst for change by promoting collective awareness and sustainable lifestyles among people to achieve holistic solutions to save the environment.